Freedom from the Stranglehold of Time: Shelley's Visionary Conception in Queen Mab. Issue 1 (April 2016) - Weinberg, Alan
Abstract : Notwithstanding ground-breaking studies of Queen Mab, the visionary scope of the work remains largely neglected. The present essay sets out to explore the vision and to show how the concern with Time is integral to it, and not just a framing device for Mab's overview of past, present and future that forms the greater substance of the whole work. The poem envisions the possibility of overcoming time's dominion or at least of coming to terms with it. The reach of the poem encompasses and extends beyond history, the repository of memory and recorded time, thus placing the attack on society within a visionary conceptualization that has no clear boundaries at all, and necessarily so. Shelley's intent is to open up discourse, to saturate his work with thinking that, from the broadest possible imaginary perspective and given his own personal stamp, disrupts time-bound presuppositions that confine human lives within the narrow limits that imprison them.